MANAJEMEN PERSEDIAAN BAHAN BAKU DODOL RUMPUT LAUT INDUSTRI â€œCITA RASAKUâ€ KELURAHAN TINGGEDE KECAMATAN MARAWOLA KABUPATEN SIGI - Abd. Mukmin,Arifuddin Lamusa, Sulaeman, Ahmad (AGROTEKBIS, 2015)
The aims of this study are the amount of raw material ordering, amount of supply raw materials and time to do a re-ordering of the raw material supply in Industry